STRATEGIC INNOVATION IN ISLAMIC ORGANIZATIONS: EXPLORING THE GOLD OCEAN STRATEGY FRAMEWORK - Adi Santoso; Yuyun Ristianawati (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2025)
This study explores the implementation of the Gold Ocean Strategy (GOS) in Islamic organizations as a novel, values-based approach to strategic management that integrates Sharia principles with ethical innovation and stakeholder collaboration. Amid growing demands for ethical governance and sustainable practices, the research aims to investigate how Islamic organizations operationalize religious values in strategic decision-making, engage with diverse stakeholders, and sustain innovation within the boundaries of Islamic law. Employing a qualitative exploratory design, data were collected through semi-structured in-depth interviews with 15 executives from three sectors—Islamic banking, halal industry, and waqf institutions—using purposive sampling. Revealed three key findings: (1) Islamic values serve as the foundation for strategic intent and organizational behavior; (2) stakeholder engagement is practiced through inclusive, trust-based mechanisms rooted in shura (consultation); and (3) innovation is actively pursued within a Sharia-compliant ethical framework, reflecting a balance between adaptability and moral responsibility. This study contributes to the literature by offering an integrative framework that synthesizes elements of the Technology Acceptance Model (TAM), Trust-Based Adoption Model (TBAM), and Expectation-Confirmation Theory (ECT) within an Islamic organizational context. The novelty of this research lies in its empirical articulation of the GOS as a strategic paradigm that is both spiritually anchored and managerially effective. The findings offer theoretical enrichment to stakeholder and innovation theories, while also providing practical insights for leaders and policymakers in promoting faith-driven, socially responsible, and innovation-oriented organizational strategies in Muslim-majority economies.